Progranulin mutation analysis: Identification of one novel mutation in exon 12 associated with frontotemporal dementia - Aswathy, P M (Neurobiol Aging, 2015)
Progranulin (PGRN) mutations account for an average of 15% of familial FTD cases and 20% of total FTD cases worldwide. Here we investigated the frequency of PGRN mutations in FTD patients (n=116) from a clinical cohort of South India and detected one novel mutation located on exon 12 in a familial bvFTD patient (accounting for ~1% of total FTD cases and 6% of familial FTD cases). This mutation was found to introduce a premature termination codon and the prematurely terminated mRNA may probably undergo nonsense-mediated decay. In ELISA, the proband showed significantly reduced level of plasma progranulin (28 ng/mL) compared with controls (150±38 ng/mL), which implicates haploinsufficiency as the pathogenic mechanism.